Systematic review and classification of: Trauma-Focused Cognitive Behavior Therapy (TF-CBT) (2. ed.) - Bjåstad, Jan Fauskanger; Haugland, Bente Storm; Kornør, Hege (Ungsinn. Journal of Effective Interventions for Children and Adolescents, 2020)
Background: Trauma-Focused Cognitive Behavior Therapy (TF-CBT) is a treatment for children and adolescents (3-18 years) who have experienced trauma, and who develops trauma related difficulties (Cohen, Mannarino & Deblinger, 2006). The treatment consists of component-based interventions to target symptoms of PTSD, anxiety, depression and other behavioral and emotional difficulties associated with traumatic experiences (Cohen, Mannarino & Deblinger, 2017). TF-CBT is a manualized treatment primarily delivered through the child and adolescent mental health service in Norway. It is delivered as an individual treatment, usually over 10-15 sessions. Parents are included in the treatment. The child and parents learn skills that can reduce stress. The goal is to manage thoughts, feelings and behaviour related to the trauma in more adaptive ways. An English treatment manual is available (Cohen, Mannarino & Deblinger, 2017) and has been translated into Norwegian (Cohen, Mannarino & Deblinger, 2018). The rights to dissemination of the program in Norway is held by the Norwegian Centre for Violence and Traumatic Stress Studies (NKVTS: www.nkvts.no). This article is a revision of a previous review of TF-CBT that was published previously in Ungsinn (Kornør, 2013). The present summary has been revised to conform to the new scoring criteria and procedures for Ungsinn (Martinussen et al., 2016). The purpose of this article is to examine whether TF-CBT is effective when used in ordinary practice in Norway. Method: The following databases were searched for articles about the intervention: EMBASE, Medline, Psykinfo, NORART, Cochrane, Cristin, NORA, SCOPUS, SweMed, The Norwegian Electronic Health Library (Helsebiblioteket.no), NREPP, NICE, Blueprints, and CEBC. In addition, the authors of the current article conducted other relevant searches. Information about the program was obtained from those responsible for the Norwegian translation and implementation of the program. Results: Results are presented in terms of the description of the program, the effects from research studies, quality of the methodology in the studies as well as for quality of the implementation of the program. The intervention is described in detail in the treatment manual (Cohen, Mannarino & Deblinger, 2017). TF-CBT has a good theoretical basis. There are numerous international effect studies and metaanalyses/systematic reviews that documents the effects of the intervention. A Norwegian RCT effectiveness study has been conducted with treatment as usual (TAU) as a control condition. This study also includes a follow up study 18 months after treatment (Jensen et al., 2014; Jensen, Holt, Ormhaug, 2017). Results suggested that youth receiving TF-CBT had significantly lower levels of posttraumatic symptoms, depression and general mental health symptoms at post-treatment compared to TAU, and that significantly fewer participants in TF-CBT were diagnosed with PTSD compared to TAU (Jensen et al., 2014). No significant differences were found between the two conditions on levels of anxiety symptoms score at post-treatment. At follow-up (18 months after treatment) youth in the TF-CBT condition maintained their symptom improvement. At follow-up, the TF-CBT group reported significantly less symptoms of general mental health problems compared to the TAU group. No significant difference was found between the two conditions on the remaining outcome variables. However, at follow-up it was found that the TF-CBT conditions had a more rapid symptom reduction and fewer treatment sessions compared to TAU (Jensen, Holt, Ormhaug, 2017). Conclusion: TF-CBT is a program with a good theoretical foundation. The intervention is described in detail. Several, well-performed international effect studies and meta-analyses/systematic reviews, as well as a Norwegian randomized controlled effectiveness trial with an 18-month follow-up study confirm the effectiveness of the program. The program is a recommended treatment in several treatment guidelines for PTSD. Systems to ensure adequate implementation quality has been developed and a Norwegian implementation plan is available. The program has been implemented in Norway with comprehensive training, supervision and fidelity checks. Based on Ungsinn’s criteria, TF-CBT applied in child and adolescent mental health clinics in Norway for youth in the age range 10-18 is classified at level 5: Interventions with strong documentation of effect. It is noted that the evidence-base for TF-CBT in Norway applies to youth in the ages 10-18 years, as no Norwegian studies are available for children below the age of 10. The evidence-base is also less clear for boys as only a minority of boys were included in the Norwegian effectiveness trial.